Assessment of the influence of turbulators in the neck of a low frequency resonator on its acoustic characteristics - O. Yu. Kustov; V. V. Palchikovskiy; I. V. Khramtsov; A. A. Kuznetsov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
The work considers low-frequency resonators with an extended neck and turbulators of different sizes, that make up a set of additional faces located on the inner surface of the resonator neck. The main goal of the work is to assess how strongly these structural elements influence the turbulization of the flow when a wave with a high sound pressure level falls on the resonator and, thereby, the dissipation of sound energy by the resonator. The studies were carried out under conditions of wave incidence normal to the front surface of the resonator. A qualitative assessment was carried out on the basis of numerical simulation of physical processes in a non-stationary formulation in an axisymmetric resonator. Quantitative assessment was based on full-scale measurements of resonators with turbulators of different sizes in a normal incidence impedance tube. The obtained results showed that for the considered variants of turbulators, an increase in their size leads to an increase in the total vorticity of the flows, and also increases the sound absorption coefficient.